2006
DOI: 10.1038/nchembio782
|View full text |Cite|
|
Sign up to set email alerts
|

Elevated levels of oxidized cholesterol metabolites in Lewy body disease brains accelerate α-synuclein fibrilization

Abstract: Oxidative stress, inflammation and alpha-synuclein overexpression confer risk for development of alpha-synucleinopathies-neurodegenerative diseases that include Parkinson disease and Lewy body dementia. Dopaminergic neurons undergo degeneration in these diseases and are particularly susceptible to oxidative stress because dopamine metabolism itself creates reactive oxygen species. Intraneuronal deposition of alpha-synuclein as amyloid fibrils or Lewy bodies is the hallmark of these diseases. Herein, we demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
273
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 323 publications
(283 citation statements)
references
References 15 publications
10
273
0
Order By: Relevance
“…Oxidation (Ko et al, 2000;Souza et al, 2000) and nitration (Giasson et al, 2000;Souza et al, 2000) of Syn, in turn, can lead to the formation of more aggregates, which could result in increased cytotoxic effects. Consistent with this, Kelly et al have shown that high levels of oxidized cholesterol metabolites in brains from PD and dementia with LB patients, accelerate Syn fibrillation (Bosco et al, 2006). On the other hand, McGeer and colleagues (Klegeris et al, 2007a) have reported that Syn-stimulated microglia, in combination with IFN-, produce and increase in the toxicity on human monocytic cells exerted by neurotoxic secretions (Klegeris et al, 2007a).…”
Section: Syn-induced Microglial Activationsupporting
confidence: 55%
“…Oxidation (Ko et al, 2000;Souza et al, 2000) and nitration (Giasson et al, 2000;Souza et al, 2000) of Syn, in turn, can lead to the formation of more aggregates, which could result in increased cytotoxic effects. Consistent with this, Kelly et al have shown that high levels of oxidized cholesterol metabolites in brains from PD and dementia with LB patients, accelerate Syn fibrillation (Bosco et al, 2006). On the other hand, McGeer and colleagues (Klegeris et al, 2007a) have reported that Syn-stimulated microglia, in combination with IFN-, produce and increase in the toxicity on human monocytic cells exerted by neurotoxic secretions (Klegeris et al, 2007a).…”
Section: Syn-induced Microglial Activationsupporting
confidence: 55%
“…Prior data indicated that cholesterol oxidation products 1 and 2, denoted 1(2) hereafter because they interconvert via an aldol/retro-aldol reaction (16,18,24), react with A␤ via Schiff base formation at the N-terminal ␣-amine of Asp-1 (D1) and the side-chain -amines of Lys-16 (K16) and Lys-28 (K28) (18). Compounds 1 and 2 have been detected by us (18,28) and others (29) in ex vivo human and rat brain samples at combined concentrations of up to 400 pg/mg of wet brain (Ϸ1 M concentration). Scheinost et al (27) recently suggested that K16 is the ''hot spot'' for A␤ aggregation induced by 1(2) modification.…”
mentioning
confidence: 99%
“…Interestingly, alterations in both of these areas are common to both Alzheimer's disease and Dementia with Lewy Bodies [52,[72][73][74].…”
Section: Discussionmentioning
confidence: 99%